Inter-Harmonics in Voltage-Sourced Converters based High Voltage Direct Current Systems - Phuc Huy Nguyen (Indonesian Journal of Electrical Engineering and Computer Science, 2015)
Voltage-Sourced Converter (VSC) is the main component in a VSC-based High Voltage Direct Current (HVDC) system. In addition to the characteristic harmonics, the inter-harmonics could be originated from the characteristic of each converter working at different modulation frequencies, or from a distorting frequency on one or both ac (or dc) systems. The space vector representation of VSC’s switching functions is used as a tool for analyzing and giving the understanding how the inter-harmonics appear. Based on the methodological analysis, simulation models were built and implemented using SimPowerSystems in MATLAB for cases. The simulation results show that, a series of inter-harmonics is produced tend to be dominant in low-frequency range, especially the negative-sequence inter-harmonics which have lower frequencies than the fundamental. This elaborate understanding of VSC-based HVDC system’s inter-harmonic characteristic could be beneficial to harmonic measurement and mitigation control. DOI: http://dx.doi.org/10.11591/telkomnika.v13i1.6809